2014
DOI: 10.1128/ec.00295-13
|View full text |Cite
|
Sign up to set email alerts
|

Role of Retrograde Trafficking in Stress Response, Host Cell Interactions, and Virulence of Candida albicans

Abstract: In Saccharomyces cerevisiae, the vacuolar protein sorting complexes Vps51/52/53/54 and Vps15/30/34/38 are essential for efficient endosome-to-Golgi complex retrograde transport. Here we investigated the function of Vps15 and Vps51, representative members of these complexes, in the stress resistance, host cell interactions, and virulence of Candida albicans. We found that C. albicans vps15⌬/⌬ and vps51⌬/⌬ mutants had abnormal vacuolar morphology, impaired retrograde protein trafficking, and dramatically increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 33 publications
3
36
0
1
Order By: Relevance
“…Susceptibility of the Cgvps15 Δ mutant to FK506 (Fig. B) is particularly intriguing as the C. albicans vps15 Δ/ vps15 Δ mutant but not the S. cerevisiae vps15 Δ mutant has recently been shown to be sensitive to FK506 (Parsons et al ., ; Liu et al ., ). These findings are suggestive of requirement for constitutive calcineurin activation in vps15 Δ mutants to be a unique feature of pathogenic yeasts.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Susceptibility of the Cgvps15 Δ mutant to FK506 (Fig. B) is particularly intriguing as the C. albicans vps15 Δ/ vps15 Δ mutant but not the S. cerevisiae vps15 Δ mutant has recently been shown to be sensitive to FK506 (Parsons et al ., ; Liu et al ., ). These findings are suggestive of requirement for constitutive calcineurin activation in vps15 Δ mutants to be a unique feature of pathogenic yeasts.…”
Section: Resultsmentioning
confidence: 97%
“…A). Notably, the hyperadherence phenotype of Cgvps15 Δ and Cgvps34 Δ mutants is contrary to the reported diminished adherence capabilities of C. albicans vps15 Δ and vps34 Δ null mutants (Bruckmann et al ., ; Liu et al ., ). Fluorescence‐activated cell sorting (FACS) analysis using anti‐Epa1 antibody showed two‐ to six‐fold higher Epa1 cell surface expression in Cgvps15 Δ and Cgvps34 Δ mutants (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Others have reported that a C. albicans vps15⌬/⌬ mutant defective in retrograde trafficking from the PVC back to the Golgi compartment is highly sensitive to fluconazole (48). Furthermore, two mutants lacking components of the endosomal sorting complex required for transport (ESCRT) that facilitates the formation of intralumenal multivesicular bodies from the PVC's surface membrane are also sensitive to fluconazole (49).…”
Section: Discussionmentioning
confidence: 99%
“…Despite also exhibiting elevated expression levels of calcineurin-dependent genes, this mutant is highly sensitive to fluconazole (37). The reasons for this are unclear; however, it is apparent that the specific PVC trafficking step affected is a crucial determinant of the physiological impact of the azoles on the fungal cell.…”
Section: Figmentioning
confidence: 98%